Chemoenzymatic semisynthesis of caffeic acid β-phenethyl ester, an antioxidative component in propolis, from raw coffee bean extract. Issue 3 (31st December 2020) - Hashimoto, Riichi; Iai, Hiyori; Fujita, Rie; Hanaya, Kengo; Higashibayashi, Shuhei; Inoue, Hiroyoshi; Sugai, Takeshi
ABSTRACT: Caffeic acid β-phenethyl ester (CAPE), an antioxidative bioactive catechol isolated from propolis, was semisynthesized from chlorogenic acid and related compounds in an extract of raw (unroasted) Robusta coffee ( Coffea canephora ) beans in 5 steps and a total yield of 31%. Oxidative degradation of the intermediates and target molecule was prevented by alkaline hydrolysis of the chlorogenic acids in the presence of sodium dithionite (Na2 S2 O4 ) and deprotection of the catecholic diacetate precursor by Candida antarctica lipase B-mediated transesterification as the final step. Graphical Abstract: